Implementation of the Game Development Life Cycle Method in Developing a Drag and Drop Educational Game for Traditional Indonesian Houses - Aulia Khoirunnita; Awang Harsa Kridalaksana; Adlina Safa Sephia Putri (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Indonesia is renowned for being a country rich in culture, one aspect of which is reflected in the diverse traditional houses found across its regions. Unfortunately, younger generations are becoming less familiar with this heritage due to monotonous and theoretical approaches in formal education. To address this issue, this study aims to develop an Android-based educational game that utilizes a drag-and-drop concept to introduce Indonesia’s traditional houses interactively. The game development process follows the Game Development Life Cycle (GDLC), consisting of six main stages: initiation, pre-production, production, testing (black box), beta testing, and release. Data were collected through a literature review of traditional houses, the GDLC method, and educational game development techniques. The resulting game, titled